Environmental Drivers of Dissolved Organic Matter Molecular Composition in the Delaware Estuary - Osterholz, Helena; Kirchman, David L.; Niggemann, Jutta; Dittmar, Thorsten (Frontiers in Earth Science, 2016)
Estuaries as connectors of freshwater and marine aquatic systems are hotspots of biogeochemical element cycling. In one of the best studied temperate estuaries, the Delaware Estuary (USA), we investigated the variability of dissolved organic matter (DOM) over five sampling cruises along the salinity gradient in August and November of 3 consecutive years. Dissolved organic carbon (DOC) concentrations were more variable in the upper reaches of the estuary (245±49 µmol L-1) than at the mouth of the estuary (129±14 µmol L-1). Bulk DOC decreased conservatively along the transect in November but was non-conservative with increased DOC concentrations mid-estuary in August. Detailed analysis of the solid-phase extractable DOM pool via ultrahigh resolution mass spectrometry (Fourier-transform ion cyclotron resonance mass spectrometry, FT-ICR-MS) revealed compositional differences at the molecular level that were not reflected in changes in concentration. Besides the mixing of terrestrial and marine endmember signatures, river discharge levels and biological activity were found to impact DOM molecular composition. DOM composition changed less between August and November than along the salinity gradient. Relative contributions of presumed photolabile DOM compounds did not reveal non-conservative behavior indicative of photochemical processing; suggesting that on the timescales of estuarine mixing photochemical removal of molecules plays a minor role in the turbid Delaware Bay. Overall, a large portion of molecular formulae overlapped between sampling campaigns and persisted during estuarine passage. Extending the analysis to the structural level via the fragmentation of molecular masses in the FT-ICR-MS cell, we found that the relative abundance of isomers along the salinity gradient did not change, indicating a high structural similarity of aquatic DOM independent of the origin. These results point towards a recalcitrant character of the DOM supplied by the Delaware River. We demonstrate that in addition to bulk DOC quantification, detailed information on molecular composition is essential for constraining sources of DOM and to identify the processes that impact estuarine DOM, thereby controlling amount and composition of DOM eventually discharged to the ocean through estuaries.